COMPARISON OF LAPAROSCOPIC AND ABDOMINAL SACROCOLPOPEXY FOR POST HYSTERECTOMY VAGINAL VAULT PROLAPSE REPAIR: META ANALYSIS - Amani, Fariska Zata; Denas, Azami; Paraton, Hari; Hardianto, Gatut; Mardiyan K, Eighty; Hartono S, Tri (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Objective: Comparing the clinical outcomes of laparoscopic and abdominal sacrocolpopexy in vaginal vault prolapse post-hysterectomy’s patient. Method: Systematic search data is performed on medical database (PUBMED, Cochrane Database) using keyword:(1) vault prolapse [title] AND (2) laparoscopic[title] AND sacrocolpopexy[title]. Inclusion criteria:(1) randomized controlled trial and observational studies, (2) women with vaginal vault prolapse post hysterectomy, (3) intervention studied: laparoscopic (LSC) and abdominal sacrocolpopexy (ASC), (4) the entire fully accessible papers can be accessed and data can be accurately analyzed. Comparison about clinical outcomes of LSC and ASC was performed using narrative analysis and meta-analysis (RevMan). Results: Three studies compared clinical outcomes of LSC and ASC with a total of 243 samples (118 in LSC and 125 in ASC group). There was no significant difference in the incidence of complications between LSC and ASC (OR 1.10;95%CI 0.58-2.08). LSC was associated with less blood loss (MD 111.64 mL,95%CI-166.13 - -57.15 mL) and shorter length of hospital stay (MD -1.82 days;95%CI -2.52- -1.12 days) but requires a longer operating time (MD 22.82 minutes,95%CI 0.43-45.22 minutes). There was no statistically significant difference to anatomical outcomes (measurement of point C on POP-Q), subjective outcomes measured by PGI-I and reoperation numbers (repeat surgical interventions) for prolapse recurrence between LSC and ASC groups after one year of follow-up. Conclusions: LSC showed similar anatomic results compared to ASC with less blood loss and shorter length of hospital stay in management patient with vaginal vault prolapse.